SITES AND SAMPLING TOOLS IN THE SOIL FERTILITY EVALUATION OF COFFEE PLANTS IN PRODUCTION - Mantovani, José Ricardo; Lima, José Antônio; Garcia, Ciro Pozzi; Rezende, Tiago Teruel (Coffee Science - ISSN 1984-3909, 2019)
In soil sampling, the collection site and the tool used may induce errors that can compromise the results of the chemical analysis and, consequently, the definition of corrective and fertilizer doses. The objective in this study was to evaluate soil sampling sites and tools in a coffee growing area. The experiment was carried out in a field in the municipality of Alfenas-MG, in a 35-year coffee field. A randomized block design was used in a 3 x 5 factorial scheme and 4 replications, totaling 60 experimental units. The treatments consisted of 3 sampling sites: in the fertilizer strip (located in the projection of the plant canopy); between rows; and in the total area, with 1/3 of the samples collected under the canopy and close to the plant stem, 1/3 in the canopy projection and 1/3 collected between rows; and 5 sampling tools: Dutch auger; screw auger; probe; hoe and drill. Soil samples were collected at a depth of 0 to 0.2 m, and each composite sample was obtained by assembling and mixing 20 single samples. At each sampling point, an area of 2m2 was delimited, in which simple samples were collected in all the evaluated places and with all the tools used. The following parameters were determined in the soil samples: pH in CaCl2; potential acidity (H+Al); organic matter; P, extracted by Mehlich; K+, Ca2+, Mg2+ and base saturation. In a coffee-growing area, he fertilizer strip (canopy projection) has topsoil with higher acidity and lower contents of organic matter and nutrients P, K+, Ca2+ and Mg2+ than between rows. The tools used for soil sampling do not influence the results of soil chemical analysis in the coffee-growing area.